Original data for 'Phenotypic plasticity in locomotor performance of a monophyletic group of weevils accords with the ‘warmer is better’ hypothesis.' published in Journal of Experimental Biology doi:10.1242/jeb.195255 - Steven Chown; Anne Treasure (2019)
Two files containing data and metadata for the study published in Journal of Experimental Biology doi:10.1242/jeb.195255 The metadata file and the data file both in comma-delimited .csv format. Data are for weevil adults walking at different temperatures after different temperature acclimation treatments. Locomotion speed is the dependent variable of interest. Different weevil species and populations from sub-Antarctic Marion Island are investigated